Petdesetletnica laserjev - Strnad, Janez (Obzornik za matematiko in fiziko, 2010)
Fifty years ago the laser era began which brought many a novelty into science, technology, and everyday life. Important steps on the way to it were the prediction of stimulated emission and the invention of the maser and the ruby and He-Ne laser.
Keywords: laser; maser; rubinski laser; stimulirano sevanje; svetloba; zgodovina fizike